FUNGSI FOLKLOR LEGENDA SUMBER TERTUA “SUMUR GEDEH” DESA PETUNG, GRESIK - Hikam, Ahmad Faruqil; Sulistyorini, Dwi (Jurnal Pembelajaran Sastra, 2025)
The Gedeh Well is one of the oldest heritage wells in Petung Village, Panceng District, Gresik Regency. The purpose of this study is to describe and examine the functions of the Gedeh Well. This study uses functional theory and a descriptive qualitative approach. The analysis examines the various forms and functions of the Gedeh Well in the Petung Village community. Then, the data is connected to the theory used. Based on the analysis, several functions of the Gedeh Well were identified: a projection system, a tool for validating rules and cultural institutions, a tool for educating children, and a tool for coercion and supervision to ensure that community norms are always adhered to by its members. The research techniques used were observation, interviews, and documentation.